Homocysteine, B Vitamins, and Cognitive Impairment - Smith, A David; Refsum, Helga (Annual review of nutrition, 2016)
Moderately elevated plasma total homocysteine (tHcy) is a strong modifiable risk factor for vascular dementia and Alzheimer's disease. Prospectively, elevated tHcy is associated with cognitive decline, white matter damage, brain atrophy, neurofibrillary tangles, and dementia. Most homocysteine-lowering trials with folate and vitamins B6 and/or B12 tested as protective agents against cognitive decline were poorly designed by including subjects unlikely to benefit during the trial period. In contrast, trials in high-risk subjects, which have taken into account the baseline B vitamin status, show a slowing of cognitive decline and of atrophy in critical brain regions, results that are consistent with modification of the Alzheimer's disease process. Homocysteine may interact with both risk factors and protective factors, thereby identifying people at risk but also providing potential strategies for early intervention. Public health steps to slow cognitive decline should be promoted in individuals who are at risk of dementia, and more trials are needed to see if simple interventions with nutrients can prevent progression to dementia.